METODE PEMBELAJARAN DISKUSI DAN SOROGAN UNTUK MENINGKATKAN KEMAMPUAN MEMBACA KITAB FATH AL-QORIB - Aliudin Aliudin; Eneng Muslihah (QATHRUNÂ, 2019)
This study aims to determine; 1) the implementation of the discussion method at the Attoyyibiyyah Islamic Boarding School, Cikande, Serang Regency 2) the implementation of the sorogan method at the Attoyyibiyyah Cikande Islamic Boarding School, Serang Regency 3) the contribution of the discussion and sorogan methods to improve the ability to read the book of fath al-qorib. 4) Comparison of the contribution of the discussion and sorogan methods to improve the ability to read the book of Fath al-qorib. This research is a mixed method research method. Respondents were 40 students, collecting data using questionnaires and tests to determine the contribution of increasing the ability to read the book of fath al-qorib. The qualitative data analysis technique used is the data triangulation technique, while the quantitative data uses statistical analysis. The results of this study are; 1) The discussion method is carried out three times a week, namely; every Saturday night, Monday night and Wednesday night at 20.00 WIB - 22.00, the book that is studied is the book "Fath Al-qorib" Implementation technique; first, the students sit in the majlis, the students who have the task of discussing the next step forward. second, begins with prayer, then reads the material to be delivered and the murody. Third, students are welcome to ask questions, then discussed, then the ustadz explains the material and finally ends with a prayer. 2) The sorogan method is carried out every Monday afternoon, the book that is studied is the book "Fath Al-qorib" Implementation technique; firstly, it was carried out by means of the students reading back the book that was read by Ustadz. second, the teacher listens to the students' reading and explanation of the material. 3) The contribution of the discussion method is 94% and the sorogan method is 40.96% 4) The contribution comparison of the discussion method and the discussion method sorogan has a greater contribution than the sorogan method.